(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
To promote the efficiency of design work, this thesis provides a renovated application tactics for theory of innovative problem solving (TRIZ) which emphasize on differences existed in design needs and targets. Its main feature is based on one characteristic in application of TRIZ in practical design where different TRIZ tools may have different instructive effects on the problems belonging to different design types.